2022
DOI: 10.1021/acs.iecr.2c03908
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Coacervate Coatings That Dramatically Improve Oxygen Barrier of Paper

Abstract: Paper-based food packaging is lightweight, low cost, and highly flexible, but it suffers from a very high oxygen transmission rate (OTR ∼ 11,100,000 cc/(m 2 •day•atm)). Herein, two polyelectrolyte-based coacervate coatings were studied as oxygen gas barriers on kraft builder's paper. A single coating deposition of a polyethylenimine-poly(acrylic acid) coacervate, adding less than 20% to the paper's weight, reduced the OTR to 164,000 cc/(m 2 • day•atm). This work not only demonstrates a significant OTR improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…This decrease is believed to be a result of a tortuous pathway blocking small ion transport through the nanocomposite. A similar phenomenon is exploited in gas barrier and anti-corrosion nanocomposites. Priolo et al reported that the oxygen transmission rate of nanobrick wall films significantly decreases as the inorganic loading increases due to the tortuous pathway. , It is important to note that the dielectric constant of the PEI/PAA + VMT system is lower than any of the systems presented, most likely due to the nanocomposite being loaded with a clay that possesses a low degree of polarization, a phenomenon that has been known to lower a composite’s dielectric constant. , …”
Section: Resultsmentioning
confidence: 96%
“…This decrease is believed to be a result of a tortuous pathway blocking small ion transport through the nanocomposite. A similar phenomenon is exploited in gas barrier and anti-corrosion nanocomposites. Priolo et al reported that the oxygen transmission rate of nanobrick wall films significantly decreases as the inorganic loading increases due to the tortuous pathway. , It is important to note that the dielectric constant of the PEI/PAA + VMT system is lower than any of the systems presented, most likely due to the nanocomposite being loaded with a clay that possesses a low degree of polarization, a phenomenon that has been known to lower a composite’s dielectric constant. , …”
Section: Resultsmentioning
confidence: 96%
“…that cause adverse environmental impacts and increase the energy cost and carbon footprint. Some emerging bio-based building blocks such as CNFs and CNCs still face challenging commercial-scale processability for coating application and drying processes due to their low solid content and high viscosity profiles; more efforts on the high solid content grade of nanocellulosic materials and their continuous coating application are being implemented to further explore their commercialization potential. , In comparison, our natural, sustainable, waterborne complex dispersion barrier coating exhibits a combination of the highest grease resistance and reduced moisture sensitivity, as well as has the promise of scale-up for industrial production (see description of scalable manufacturing of complex dispersions in the Supporting Information). Moreover, our material selection and one-pot processing pathway align well with green chemistry principles such as use of renewable feedstocks, benign solvents, design for energy efficiency, and design for degradation …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we envision that the developed polysaccharide complex barrier coating would be beneficial to the improvement of oxygen barrier performance of the fiber-based or flexible packaging and the shelf-life extension of perishable fruits, which would need further investigation in future work. Indeed, literature works have confirmed that an intimate ionic crosslinking network structure creates superior resistance to oxygen permeation, leading to a high oxygen barrier coating for flexible (biaxially oriented polypropylene) 43 and fiber-based 44 packaging substrates, as well as a protective layer to slow down the ripening or browning of fruits. 45 Figure 6e shows photographs of the liquid barrier performance of paperboard substrates coated with 7.8% complex dispersion.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thin, flexible, coatings with high oxygen barrier are widely used for improving the shelf life of flexible organic electronics and perishable food products. [1][2][3] Improving the barrier performance of food packaging is particularly important, as every year a staggering 30% of food products are wasted in the United States. [4] Vapor deposited inorganics (SiO x and Al 2 O 3 ) provide remarkable barrier performance, but suffer from pinholes, cracking DOI: 10.1002/mame.202300407 when flexed, and complex/expensive processing conditions (e.g., vacuum /nonambient).…”
Section: Introductionmentioning
confidence: 99%